Fleksibilitas dan Kepastian Hukum dalam Ekonomi Islam: Analisis Kaidah Al-Ma’ruf ‘Urfan Kal-Mashrut Shartan - Muhammad Louis Nawafil; Tyan Restiyani (Journal of Fiqh in Contemporary Financial Transactions, 2026)
This study aims to analyze the meaning of the fiqh principle "Al-Ma’ruf ‘Urfan Kal-Mashrut Shartan" and its practical implementation in contemporary muamalah maliyah transactions. This research uses a qualitative approach with library research methods and analysis of classical and contemporary fiqh texts. The results show that social traditions or norms ('urf) that are widely recognized have the same legal force as written conditions in a contract, provided they do not conflict with sharia. This study integrates the application of 'urf principles within the context of dynamic modern Islamic economic transactions. This principle provides legal flexibility for transacting parties while maintaining the principle of legal certainty in Islamic economics.